Pulmonary benign metastasizing leiomyoma in patients aged 45 years and younger: clinical features and novelty in treatment - Hao Su; Rong Fan; Hua Yang; Yan You; Lan Zhu; Fengzhi Feng (BMC Pulmonary Medicine, 2023)
Abstract Background Pulmonary benign metastasizing leiomyoma (PBML) is the most common extrauterine spread of uterine leiomyoma, and its biological behavior is traditionally thought to be hormone dependent. Studies on older PBML patients have been previously reported, but limited literature has been published regarding the clinical features and treatment of PBML in young women. Methods A total of 65 cases of PBML in women aged 45 years and younger were reviewed, including 56 cases selected from PubMed and 9 cases from our hospital. The clinical characteristics and management of these patients were analyzed. Results The median age of all the patients at diagnosis was 39.0 years. PBML most commonly presented as bilateral solid lesions (60.9%), with other rare imaging manifestations. The median interval time from a pertinent gynecologic procedure to diagnosis was 6.0 years. A total of 16.7% of patients received careful observation, and all achieved stable status in a median follow-up time of 18.0 months. A total of 71.4% of patients were administered anti-estrogen therapies, including surgical castration (33.3%), gonadotropin-releasing hormone analog (23.8%) and anti-estrogen drugs (14.3%). Eight of 42 patients underwent surgical resection of metastatic lesions. Patients who underwent curative surgery for the removal of pulmonary lesions combined with adjuvant anti-estrogen therapies had favorable outcomes compared with those who only underwent surgical resection. The disease control rates of surgical castration, gonadotropin-releasing hormone analog, and anti-estrogen drugs were 85.7%, 90.0%, and 50.0%, respectively. For two patients, sirolimus (rapamycin) achieved successful relief of symptoms and control of pulmonary lesions without lowering hormone levels and causing estrogen deficiency symptoms. Conclusions In the absence of standard treatment guidelines for PBML, maintaining a low-estrogen environment using different kinds of antiestrogen therapies has been the mainstream strategy and has satisfying curative effects. A wait-and-see strategy might be an option, but therapeutic approaches must be contemplated when complications or symptoms progress. For PBML in young women, the negative effect on ovarian function of anti-estrogen treatment, especially surgical castration, should be considered. Sirolimus might be a new treatment option for young PBML patients, especially for those who want to preserve ovarian function.